50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-3453
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental study on the Solid Fuel Scramjet Combustor with a cavity flame holder

Abstract: The specific thrust level and variation rule of solid fuel scramjet combustor were researched both by numerical and experimental methods. A methane-burning vitiated air heater was designed and made to simulate flight environment of Mach 6 at 25km altitude. Based on the two dimensional flow field structures, a new quasi-one dimensional numerical method was established. The typical unsteady matter of solid fuel scramjet combustion and flow was transformed into a steady calculation of every moment in this method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, most of them were focused on the side wall injection form, which injects the fuel-rich primary gas into the combustor from the inner wall position and enhances the mixing by adjusting the injection angle or adopting different cavity structures. There are some problems in this injection form, such as the large total pressure loss, uneven combustion heat release, and easy ablation of the cavity [27][28][29]. Therefore, in this paper, a new scheme of solid rocket scramjet based on the central strut injection was proposed, and the ground experiment and numerical simulation with different equivalence ratios under the flight condition of Mach 6, 25 km were carried out.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of them were focused on the side wall injection form, which injects the fuel-rich primary gas into the combustor from the inner wall position and enhances the mixing by adjusting the injection angle or adopting different cavity structures. There are some problems in this injection form, such as the large total pressure loss, uneven combustion heat release, and easy ablation of the cavity [27][28][29]. Therefore, in this paper, a new scheme of solid rocket scramjet based on the central strut injection was proposed, and the ground experiment and numerical simulation with different equivalence ratios under the flight condition of Mach 6, 25 km were carried out.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with the liquid fuel scramjets, solid fuel scramjets have the same advantages as traditional solid fuel engines, such as simple structure, high energy density, good maneuverability, and long storage time, etc. Therefore, the solid fuel scramjet has gradually developed in the recent decades [13,[19][20][21][22][23][24][25][26][27][28][29][30][31]. Main achievements of the solid fuel scramjet are summarized below.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the total pressure recovery and the combustion efficiency was 35% and 48%, respectively. Wang et al [24,25] conducted numerical and experimental studies on the specific thrust level and variation rule in the solid fuel scramjet combustor. The results pointed out that the specific thrust could reach about 600-800 N/kg•s in the preconcerted flight conditions, and the specific thrust decreased with the total pressure recovery increase during the operating process.…”
Section: Introductionmentioning
confidence: 99%